Prevalence of permanent tooth loss among children and adults in a suburban area of Chennai - Benley George; Joseph John; S Saravanan; I Meignana Arumugham (Wolters Kluwer Medknow Publications, 2011)
Aim: To determine the prevalence of permanent tooth loss among children and adults in a suburban area of Chennai. Design: Cross sectional descriptive study. Study setting: The study was conducted in Tiruverkadu, a suburban area of Chennai. Materials and Methods: A house-to-house survey was done in Tiruverkadu. The study population consisted of 6, 12, 15 years children, 35-44 years, and 65-74 years adults. Type III dental examination was carried out. Cross tabulations and Chi-square statistics were computed. The level of significance was chosen as P<0.05. Results: Out of the total 679 subjects, 309 subjects had tooth loss. Females (47.9%) had greater tooth loss compared to males (42.9%). Tooth loss increased as age progressed. Subjects in the lower socio-economic status had greatest tooth loss. The mean tooth loss among the subjects was 2.7. Conclusion: This study indicates that tooth loss increases with age and differs for gender and socio-economic status. The prevalence of tooth loss among the subjects was found to be high in children as well as in adults. Therefore, dental professionals should utilize various measures available in preventive dentistry to minimize tooth loss.